2020
DOI: 10.1108/mf-05-2020-0275
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 countermeasures, sporting events, and the financial impacts to the North American leagues

Abstract: PurposeThe purpose of this paper is to analyze how the coronavirus disease 2019 (COVID-19) countermeasures will affect the financing of the North American leagues. In particular, we focus on the missed revenue from gate receipts for the Big Four leagues.Design/methodology/approachThe authors forecast the 2020 revenue for each of the four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Reimbursement of money after the postponement and cancellation of sporting events and the lack of revenues were emphasized in some tweets. A recent study showed how the Big Four League in North America supposed a potential revenue fallout of 6bn dollars if they did not collect any gate receipts until the end of the season [ 66 ]. However, many other economic facets are mentioned in our data on the reduction of income from sponsors, broadcast revenues, merchandising, and travel and accommodation, which may produce an extension fallout to the tune of 160bn dollars [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reimbursement of money after the postponement and cancellation of sporting events and the lack of revenues were emphasized in some tweets. A recent study showed how the Big Four League in North America supposed a potential revenue fallout of 6bn dollars if they did not collect any gate receipts until the end of the season [ 66 ]. However, many other economic facets are mentioned in our data on the reduction of income from sponsors, broadcast revenues, merchandising, and travel and accommodation, which may produce an extension fallout to the tune of 160bn dollars [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…For human resources part, researchers' attention mainly focused on the employment situations and the general impacts and fluctuations in labor market (Kaur et al, 2020;Modrego et al, 2020;Webb et al, 2020). For the economic impacts on sports (Drewes et al, 2021;Ehrlich et al, 2020), most of the researchers discussed the operation of football club or the leagues (Ehrlich et al, 2020). As the most basic industry, the pandemic's economic impacts on agriculture are huge.…”
Section: The Analyses Of the Pandemic's Economic Impacts On Different Industriesmentioning
confidence: 99%
“…By March 2020, COVID-19 has already reached to every country in MENA region and disrupted the economic activities. The first COVID-19 case in MENA was detected in United Arab Emirates (UAE), when a four-member family with a travel history to China was found COVID-19 positive in January 2020 (Ehrlich, Ghimire, Khraiche, & Raza, 2020). MENA countries are characterized by the varying level of health and other economic infrastructure across the region.…”
Section: Introductionmentioning
confidence: 99%